Não é TV Estratégias Comunicacionais da HBO no Contexto das Redes Digitais - Santos, Maíra Bianchini dos (2012)
Understanding the communication strategies adopted by U.S. television network HBO in the context of digital networks is the goal of this study. The case study contemplates the online and at a distance observation of an intentional sampling which covers multiple products and services of the network along its history. In the first part of the paper, HBO s strategic course is studied from the perspective of Reeves, Rogers and Epstein (1996, 2002, 2006, 2007) about the ages of TV I, II and III. HBO was the first U.S. cable network to offer exclusive content to its subscribers and, later, initiated the production of made for TV movies, series and miniseries among the subscription-based television networks. The second part of the research discusses the strategies used by HBO starting from the mid-2000s, when the network starts to consider the digital landscape in which the flow of content produced by television networks and the mutual exchanges by the public occur among multiple media platforms (Lotz, 2007; Gabriel 2010). The strategic actions of HBO point to some of the characteristics of the current television context, which includes strategies that encourage active participation and conversation among viewers in digital networks, the strengthening of the television network s own digital presence and the search for complementary platforms for content distribution and for additional sources of income in the context of the Long Tail (Anderson, 2006). The strategies adopted by HBO in the last decade allows us to identify the specific dynamics that rule television in the convergence culture (Jenkins, 2008), which characterize the fourth phase of American television proposed in this study, the age of TV IV.